Entry Mode Choice in Doing Business in Indonesia - Hadijanto, Sari Shaviriyani (2006)
As one of the world's largest emerging market, Indonesia has attracted a significant amount of foreign direct investments (FDI) since the "open door" policy in 1967. The overall trend in foreign investments has led to high growth in Indonesia's industry which consist nearly 66 % of the cumulative FDI from 1967 to 1996. However, Indonesia's investment climate is still poor as Indonesia was ranked 97th out of 102 countries in the World's competitiveness forum in 1993. In contrast, it is believed Indonesia is very potential country with large growth market, abundant numbers of natural resources and cheap labor costs. The heavy dependence on these factors is meaningless if the Indonesian government itself does not support it with the appropriate infrastructure and technology capabilities. Moreover, the situation was worsened when FDI also declined gradually since 1997-1998 financial crisis. While most of Indonesians look at this trend with great concern and worries, in the other hand, most of the foreign investors perceived this as an opportunity for trading and investment prospects as they are able to put investment with the fewer amounts since the collapse of Indonesian rupiah led to the stronger value of dollars. This study attempts to find out the determinant factors contributing to entry mode decision in Indonesia by foreign investors. We reviewed various theoretical aspects of FDI and extracted a number of factors from various previous researches that became our proposed hypotheses. Empirical studies by various researchers on determinants of entry mode in Indonesia provide the variables for our regression tests analysis. Explanatory study by way of quantitative approach was used for this research. Variables were determined with an ex post facto design that is the researcher has no control over the variables in the sense of being able to manipulate them. The purpose of the study itself is attempting to explain relationship among variables or it is called causal study. Longitudinal studies are carried over the time on the same sample. Lastly, the statistical studies are designed by using regression test on the hypothesis quantitatively so that we can capture generalization about findings based on representative ness of the sample of number of foreign companies that has been investing in Indonesia. Our study reveals that all foreign companies invested in Indonesia do exporting form, rather than investing in equity form. Therefore, many of proposed hypotheses might not valid to some of host countries, as the determinant factors are mostly contributing to equity mode investment. Yet, some countries perceive several proposed variables were important to their entry mode selection regardless to their preference of FDI location in Indonesia. Finally, we provide some strategic directions to the Indonesian policy makers and managers who ran foreign business in Indonesia, and then we provide limitation of this study and suggest areas for further research.